PENGARUH PEMBERIAN ABU BOILER TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L.) DI LAHAN GAMBUT - Yeni Hartati; Nelvia Nelvia (DINAMIKA PERTANIAN, 2017)
The aim of research to study the effect of Boiler ash origin palm oil mills (PKS) and the pulp on growth and yield of onion (Allium ascalonicum L.) on peatland. Research conducted at the experimental farm, Faculty of Agriculture, University of Riau, Rimbo Panjang village, Kampar District, Riau Province from August to November 2015. The study using the split-plot design (Split Plot Design), as the main plot, Boiler ash consists of two levels (plant origin MCC and pulp), and the subplot is boiler ash doses (0, 3, 6, and 9 tons/ha). Parameters measured were plant height, tuber number, the weight of tuber per hill, and tuber yield per m2. The results showed that plant height increased markedly in the application of 3 tons/ha ash from two sources, the number of tubers per clump sample increased markedly on the application of 6 tons/ha ash from PKS, as well as tuber weight per hill and tuber yield per m2 tends to increase with the application 3-9 tonnes/ha, the increase is greater with higher doses of ash from both sources.